Chapter Self-healing of Structural Composites Containing Dendrimers as Healing Agent - Kotrotsos, Athanasios (InTechOpen, 2018)
Dendrimers exhibit healing functionalities on polymer level. In the present chapter, the effect of hydrogen-bonded supramolecular polymers (SP) into high performance aerospace carbon fiber reinforced plastics (CFRPs) is assessed. More precisely, the interlaminar fracture toughness of unidirectional (UD) SP-modified composites (containing SP interleaves) and their healing capability were measured under mode I and mode II fracture loading conditions. During testing, these modified samples exhibited extended bridging between the interlaminar crack flanks, which considerably enhanced their interlaminar fracture toughness. Furthermore, SP pre-impregnated fiber layers (prepregs) were fabricated to facilitate the introduction of the self-healing agent (SHA) into the composite laminated structure. SP prepregs were used to modify quasi-isotropic CFRPs in a symmetric fashion, and the damage tolerance of the modified composites was investigated. To that direction, the SP-modified laminates were tested under low velocity impact (LVI) conditions, and compression after impact (CAI) tests were conducted prior and after the activation of the healing. Finally, examination of the morphology of fracture surface led to qualitative conclusions regarding the involved failure and healing mechanisms.